HUBUNGAN PENDIDIKAN, KETERPAPARAN INFORMASI DAN PARITAS DENGAN TINGKAT PENGETAHUAN MANAJEMEN LAKTASI PADA IBU PASCA SALIN DI RUANG NIPAS RUMAH SAKIT UMUM DAERAH KOTA MAKASSAR - Desi Eka Prawtiwi (Stikes Graha Edukasi Makassar, 2021)
Lactation management is one of the program efforts of MCH (Maternal and Child Health). If lactation management is not implemented, it will have an impact on reducing breastfeeding, resulting in an increase in malnutrition and malnutrition, which in turn will lead to an increase in morbidity and infant mortality. The aim of this study was to determine the relationship between education, exposure to information and parity with the level of knowledge of lactation management among postpartum mothers in the postpartum ward at the Makassar City regional general hospital. This research method uses analytical research methods with a